Parental factors associated with obesity in children with disability: a systematic review. Issue 7 (25th March 2013) - McGillivray, J.; McVilly, K.; Skouteris, H.; Boganin, C.
Summary The current literature on obesity in typically developing children shows that the family context, and specifically the way parents parent their children are major determinants of childhood obesity. The influence of these factors on obesity in children with disability, however, remains unclear. A systematic review of the literature was undertaken to identify the parental and parenting risk factors associated with obesity in children and adolescents with disability. Articles were identified through Medline, Academic Search Complete, PsycINFO, ProQuest, ISI, CINAHL, Cochrane and Scopus databases. There was no restriction on publication dates. The inclusion criteria were empirical papers that tested associations between parental and parenting risk factors and obesity in children and adolescents with intellectual and other developmental disabilities. Only 11 studies met the selection criteria and subsequently included in this review. Results suggest that obesity in children and adolescents with disability may be associated with socioeconomic status; parents' body mass index, perception and attitude towards their children's weight and physical activity; and levels of activity in both parents and children. Firm conclusions about these associations cannot be reached, however, due to mixed findings and methodological limitations of the studies. Recommendations for future research are provided.